Sistem Informasi Buku Induk Siswa Pada SMA Negeri 1 Kelekar - Iski Zaliman; A. Taqwa Martadinata; Agustina Heryati; Dwi Yuny Sylfania (Jurnal Informatika Global, 2022)
Public and Private Schools must always develop to improve the quality of education with professional service to school residents. Information Technology will produce a well-computerized system to support human resources with performance in management tasks. The Student Parent Book information system is the most important thing in education in order to fulfill the need for information for students so that the process of making reports and recording administrative data at SMA Negeri 1 Kelekar can be even better. With the existing system, it will provide menu features that exist in the unit category component or an information and will be obtained as a guide for students, SMA Negeri 1 Kelekar currently uses, manages and stores student data in the Parent Book. Not yet computerized in data processing. Students, there will be a risk that it will be difficult to find information on student data identity and the creation of a student data report that has been recorded in the student main book. The information system at SMA Negeri 1 Kelekar which will build a new system will be very useful, this information system will be designed as a web-based system that is more easily accessible, in order to provide benefits for the school, especially the School Administration Staff so that they can use the information system in accordance with future needs. All the menu features available in this system are to facilitate the process of recording and reporting the student master book, so that it can be accelerated in searching for student data at SMA Negeri 1 Kelekar in using the existing student master book process that is available to run well and smoothly.Keywords : System, Master Book, Web Based, PHP and MySQL